Determination of landfill sites in Kirkuk district using remote sensing and geographic information systems - Daeij, Mona Ali; Abdul Hussein, Hussein Kazem (Journal of engineering sciences and information technology, 2017)
The study aims at determining the landfill sites in Kirkuk governorate in northern Iraq, specifically in the north-east of the governorate. The area of ​​the basin is 162.1 km 2. A number of criteria have been studied, including natural (linear structures, gradient, rivers, groundwater), human (urban areas, villages, roads) and the nature of the land (vegetation density), which determine the degree of relevance of the landfill Affected by landfills through the health and environmental problems that cause these standards to interact.Based on these criteria, a model was constructed to determine the suitability of all areas of the research area, which were divided into categories that showed that the areas suitable for the establishment of sanitary landfill sites amounted to (1370.69 km2), ie 41.45% of the total area. Areas where no natural landfill sites can be constructed according to natural and human criteria and the nature of the land was (1178.43 km 2), or 35.64% of the total area of ​​the area.
Keywords: remote sensing